2005
DOI: 10.1158/1055-9965.epi-03-0493
|View full text |Cite
|
Sign up to set email alerts
|

Use of Colonoscopy for Colorectal Cancer Screening: Evidence from the 2000 National Health Interview Survey

Abstract: Background: The use of colonoscopy as a primary screening tool for colorectal cancer is gaining momentum owing to several studies suggesting superior effectiveness and the recent, favorable decision by Medicare to cover all routine screening colonoscopies. This study documents the use of colonoscopy versus other tests to screen for colorectal cancer. Materials and Methods: Data from the 2000 National Health Interview Survey were analyzed. Fecal occult blood test (FOBT), sigmoidoscopy, and colonoscopy done for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
47
0
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 26 publications
5
47
0
3
Order By: Relevance
“…Smokers declared almost twice as low readiness for screening, which may have its roots in their lifestyle associated with a more nihilistic attitude toward health. Similar conclusions were drawn by American authors, who found that smokers and alcohol abusers are less eager to participate in screening [34,35]. These observations lead to the conclusion that a great er emphasis should be placed on the need to screen men, obese persons, smokers and alcohol abusers.…”
supporting
confidence: 77%
“…Smokers declared almost twice as low readiness for screening, which may have its roots in their lifestyle associated with a more nihilistic attitude toward health. Similar conclusions were drawn by American authors, who found that smokers and alcohol abusers are less eager to participate in screening [34,35]. These observations lead to the conclusion that a great er emphasis should be placed on the need to screen men, obese persons, smokers and alcohol abusers.…”
supporting
confidence: 77%
“…According to US national estimates, only 31% of Hispanics undergo either colonoscopy or sigmoidoscopy as screening procedure for colorectal cancer compared to 35% African Americans and 39% Whites. 12 Of all subjects who underwent colonoscopy in our study, a majority of them (85%) were Hispanics. This represents colorectal cancer screening in an estimated 21% of our eligible Hispanic American subjects by colonoscopy alone.…”
Section: Colonoscopy Accessmentioning
confidence: 77%
“…12 The reported rate of screening for colorectal cancer by colonoscopy in adult practice settings is only about 12.5%. 14 Using the system interventions described earlier, the overall colorectal screening coverage provided by our facility among persons aged 50 and over in surrounding ZIP codes increased from 5.2% to 15.6%.…”
Section: Colonoscopy Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…Presently, there are five advocated options for elective screening in asymptomatic patients: 1) yearly stool testing for occult blood starting at age 50, 2) an air-contrast barium enema of the large bowel at age 50 and every five years thereafter if the findings are normal, 3) flexible sigmoidoscopy (FS) at age 50 and every five years thereafter if the findings are normal, 4) computed tomography colonography at age 50 and every five years thereafter if the findings are normal, and 5) colonoscopy at age 50 and every ten years thereafter if the findings are normal. 2,3 The main focus of this analysis revolved around the use of FS within this asymptomatic screening population, and specifically, whether further evaluation (colonoscopy) should be considered in patients found to have distal hyperplastic…”
Section: Introductionmentioning
confidence: 99%